Debatendo a educação rural no Brasil : as ações das comunidades locais e escolares para manter em funcionamento as escolas rurais em Piracanjuba/GO - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Considering the population of Piracanjuba and the national reality that expresses the process of closing schools in rural areas, we can say that the municipality currently has a reasonable number of schools in operation. For the development of this research, we established as a general objective to investigate the actions taken by local communities and schools of the five remaining rural schools in the municipality of Piracanjuba to keep them functioning in the face of the opposite impositions of the municipal executive power. This context allowed us to recognize the complexes of relationships that marked the attempts to close rural schools in Piracanjuba, as well as the clashes and conflicts that materialize in this territory, adding to them the relationship between man and school in rural areas and with the other men. We took as a starting point the bibliographical review and the collection of official documents in the perspective of selecting the sources to carry out our research on rural schools in the municipality. Initially, we note that studies on this theme involve several areas of knowledge. Our preliminary analyzes of theselected sources pointed out that academic production on rural education and rural education, although recent, takes place through the examination of the subject's own reality, against the hegemony of capital and the closing of schools in the middle. As amethodological instrument to carry out the field research, we used semi-structured questionnaires applied to nine teachers from five rural schools in the municipality. We verified that the arguments defended in the last administrations of the municipal executive power of Piracanjuba in defense of closing schools in rural areas are concentrated on the assumption that demand is low –reducednumber of students per school –na occurrence that increases “expenses”with maintenance of physical, material, human, didactic-pedagogical resources, making the application of public financial resources unfeasible, becoming costly and, in this sense, the option found was the use of school transport to take children and adolescents from rural areas to the urban schools. However, as we observed in the voices of the interviewed teachers, it is quite possible that the daily school transport of students to the urban area, in fact, implies a “waste of public resources” and not an investment in maintaining schools in rural areas.
Debating rural education in Brazil: actions by local and school communities to keep rural schools in Piracanjuba /GO operational
Keywords: Escola rural; Educação do campo; Transporte escolar; Luta e resistência; Rural School; Countryside education; School transport; Struggle and resistance.; CIENCIAS HUMANAS::HISTORIA